Jenis-jenis Tumbuhan yang Dimanfaatkan sebagai Obat Tradisional di Kecamatan Lubuk Tarok Kabupaten Sawahlunto Sijunjung - Darmanella Dian Eka Wati (Pendidikan Biologi FKIP UMMY, 2019)
The government strives to realize development in the field of health as a whole, integrated and affordable by all levels of society through the